The Effect of Learning Model-Based Integrated Webbed Scientific Type of Learning Outcomesa in Class IV SDN Gugus II Kecamatan Batang Anai - Suhernisa MY; Solfema Solfema; Yanti Fitria; Hendra Syarifuddin (International Journal of Educational Dynamics, 2019)
Mathematics learning has so far not developed students' ability to solve problems. This can be seen from the difficulties of students in solving problems found in mathematics subjects. The purpose of this study in general is to examine the effect of PBL models and learning motivation on the mathematics learning outcomes of Class IV of SD Negeri 1 Batang Anai District, Batang Anai District, Pariaman Regency. The method used was a quasi-experimental design with 2x2 factorial design. The experimental and control groups were recruited by purposive random sampling. Data were analyzed by two-way variance t-test and analysis. The results showed that there were significant differences in learning outcomes between students taught with PBL models rather than students taught with conventional approaches, and between groups of students who were high and low motivated learning. There is no significant interaction between PBL models and learning motivation towards learning outcomes.